Religiosity and religious crises of medical students and their opinions on the usefulness of chaplains' service and religion in coping with illness - Joanna Żołnierz; Jarosław Sak; Agnieszka Brzozowska (Kazimierz Wielki University, 2017)
Aim: The aim of the study was to obtain information on the religiosity of medical students, including the occurrence of the phenomenon of religious crisis. The paper also attempts to verify whether there is a relationship between the centrality of religiosity and the way to answer questions about the usefulness of ministry of chaplains and the role of religion in coping with illness. Method: The study was conducted among 273 medical students, aged 19-27. Data was obtained using Scale of the Religious Crisis by W. Prężyny (SKR), Scale of Centrality of the Religions of S. Huber in translation of  B. Zarzycka and a self-devised questionnaire. Results: Respondents who were convinced that religion and contact with the chaplain helps to cope with life difficulties, compared to those who believed that religion rather helps, or those who thought religion does not help, experience a religious crisis less often. In the groups of people who believed that religion and the priest's in-hospital contact definitely helps to cope with the disease, in comparison to those who thought it rather helps or than those who thought it does not help, a higher centrality of religiosity in the various subscales was observed.   Conclusion: Studies have shown that students who do not attribute religion and chaplaincy to a large role in coping with life problems experience a religious crisis more often than those who do not experience crises. Respondents who believed that both religion and priest's in-hospital contact help in coping with difficulties were characterized by high frequency of personal religious practices.